2013
DOI: 10.1016/j.medengphy.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Computation of full-field displacements in a scaffold implant using digital volume correlation and finite element analysis

Abstract: Measurements of three-dimensional displacements in a scaffold implant under uniaxial compression have been obtained by two Digital Volume Correlation (DVC) methods, and compared with those obtained from micro-finite element models. The DVC methods were based on two approaches, a local approach which registers independent small volumes and yields discontinuous displacement fields; and a global approach where the registration is performed on the whole volume of interest, leading to continuous displacement fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 53 publications
(91 reference statements)
2
61
0
1
Order By: Relevance
“…40 In the case of the FFT-based DIC algorithm used here, the period of the oscillation due to interpolation bias corresponds to a displacement equivalent to 2 voxels. [44][45][46] This is consistent with 2.5 fringes observed in Fig. 8(b) for a total deformation corresponding to 5 voxels.…”
Section: Dvc Results For Rectangular Phantom Stripsupporting
confidence: 90%
“…40 In the case of the FFT-based DIC algorithm used here, the period of the oscillation due to interpolation bias corresponds to a displacement equivalent to 2 voxels. [44][45][46] This is consistent with 2.5 fringes observed in Fig. 8(b) for a total deformation corresponding to 5 voxels.…”
Section: Dvc Results For Rectangular Phantom Stripsupporting
confidence: 90%
“…Given that the vector fields have been shown to be incorrect in this case, the strain resolution will be evaluated from the stationary and y-displaced scans. Previous studies have shown that any rigid body translation tests will cause an increase in strain standard deviation because of the additional errors from the interpolation biases due to the specimen movement [30], [26]. Although this is true for the z-displaced results, the y-displaced values are consistently lower than the stationary tests.…”
Section: -Stationary Resultsmentioning
confidence: 79%
“…Yet, another approach that combines repeated µCT images and digital volume correlation (DVC) techniques has been developed recently to study the mechanical behaviour of whole vertebrae (Hussein et al, 2012), trabecular bone (Bay et al, 1999;Bremand et al, 2008;Gillard et al, 2014;Liu and Morgan, 2007;Zauel et al, 2006), scaffolds (Madi et al, 2013) and bone implant interface (Basler et al, 2011). These deformable registration approaches can provide an estimation of the distribution of displacements and strains between two 3D images of the sample before and after a certain deformation is applied.…”
Section: Introductionmentioning
confidence: 99%